2019
DOI: 10.1002/cbdv.201800518
|View full text |Cite
|
Sign up to set email alerts
|

Covalent vs. Non‐Covalent Inhibition: Tackling Drug Resistance in EGFR – A Thorough Dynamic Perspective

Abstract: A persistent challenge in the treatment of non‐small cell lung cancer (NSCLC) with EGFR is the emergence of drug‐resistant caused by somatic mutations. The EGFR L858R/T790 M double mutant (EGFRDM) was found to be the most alarming variant. Despite the development of a wide range of inhibitors, none of them could inhibit EGFRDM effectively. Recently, 11h and 45a, have been found to be potent inhibitors against EGFRDM through two distinctive mechanisms, non‐covalent and covalent binding, respectively. However, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 77 publications
0
11
0
Order By: Relevance
“…Recently, several covalent agents targeting surface Cys residues have entered clinical studies in oncology. , Based on this success and expanding on the relatively limited target space of the Cysteinome, we and others propose the introduction of suitable electrophiles to target other residues. ,,,, Our own recent studies ,, and others , suggested that it is possible to target Lys residues located at protein–protein interfaces, in principle expanding the target space of covalent antagonists to protein–protein interactions (PPIs) that have a Lys in the vicinity of their binding sites. , We recently found that certain substituted aryl-sulfonyl fluorides, namely, as in compounds 1 or 2 (Table ), possess a more balanced reactivity and stability in aqueous buffer and in cell, and hence, they can be used as electrophiles in pharmacological tools and perhaps future therapeutics . These previous studies were conducted targeting the BIR3 domains of XIAP, cIAP1, or cIAP2.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, several covalent agents targeting surface Cys residues have entered clinical studies in oncology. , Based on this success and expanding on the relatively limited target space of the Cysteinome, we and others propose the introduction of suitable electrophiles to target other residues. ,,,, Our own recent studies ,, and others , suggested that it is possible to target Lys residues located at protein–protein interfaces, in principle expanding the target space of covalent antagonists to protein–protein interactions (PPIs) that have a Lys in the vicinity of their binding sites. , We recently found that certain substituted aryl-sulfonyl fluorides, namely, as in compounds 1 or 2 (Table ), possess a more balanced reactivity and stability in aqueous buffer and in cell, and hence, they can be used as electrophiles in pharmacological tools and perhaps future therapeutics . These previous studies were conducted targeting the BIR3 domains of XIAP, cIAP1, or cIAP2.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the type of inhibition of the EGFR kinase activity, the approved EGFR-TKIs can also be classified as reversible and irreversible inhibitors, as shown in Figure 5. For the first type, the inhibitors competitively bind to the ATP binding site in the EGFR through noncovalent interactions involving electrostatic, hydrogen-bonding, and hydrophobic interactions [24].…”
Section: Classification Based On the Types Of Interaction With Egfrmentioning
confidence: 99%
“…The extent to which the compounds bind to the RdRp-NSP complex was determined using the MM/PBSA method. 37,38 Stable time-frames (170-200ns) were also selected to minimize entropical effects and our results are presented in Table 1. Accordingly, Rem-P 3 was strongly bound than ATP with ∆G bind difference of -13.2 kcal mol -1 .…”
Section: Binding Free Energy Calculations and Decompositionmentioning
confidence: 99%